Simulation of multi fluid gas turbines - Ulizar Alvarez., J. I. (Cranfield University, 1998)
This work focuses on two main subjects: first, the development and validation of a robust generic performance code for industrial gas turbines (GTSI) and, second, the study of an innovative carbon dioxide/argon semi-closed cycle burning low calorific gas coming from coal gasification. GTSI will be able to simulate open, closed and semi-closed cycles at design and off-design conditions. A comprehensive thermodynamic study of the properties of the most common working fluids has been carried out, introducing the results in GTSI for a wide range of temperatures and pressures, being easy to add other gases. To make the code very general, in addition to gas turbines conventional components, such as inlet, compressor,, intercooler, regenerator, combustor, turbine and exhaust system, GTSI can model evaporative intercooler, steam injection and reheat. The possibility of variable geometry was introduced in the compressor, steam injector and turbine modules. Given the high temperatures in modem and future turbines, a detailed cooling system modeling has been developed, being able to predict cooling flow requirements according to different technology levels. The control of the complete power plant has also been considered in detail, allowing the user to select among different options. The code incorporates a simple steam turbine bottoming cycle for a preliminary analysis of the combined cycle arrangement. In addition to the conventional off-design simulations it is possible to carry out studies involving engine deterioration and modification, or substitution, of components. A validation process was carried out using different gas turbine arrangements. The result has been satisfactory, although additional configurations should be examined when more data is available. As a direct application of GTSI, the conceptual design of the carbon dioxide/argon semi-closed cycle was conducted. Several key performance factors were considered in this study, such as the working fluid composition, the gas turbine arrangement and the cooling technology. Other main parameters were selected according to the state-of-the-art technology. Advanced concepts such as cryogenic precooling and turbine stator internal cooling, together with improved component efficiencies and higher temperatures were contemplated for a mid-long term future design. The results obtained for the conventional cycles have not been very promising, with slightly better values for the advanced cycles. Five of the most interesting cycles were selected for off-design studies, evaluating the part-power behaviour, the variable geometry requirement, etc. To complete the investigation, the starting sequence of one of them was performed. Also, considering the possibility of using existing turbomachinery, designed for air, in a semi-closed cycle pilot plant, the operation of several gas turbine configurations was analysed.